AVALIAÇÃO DA DENSIDADE MINERAL ÓSSEA, ESTADO NUTRICIONAL E COMPOSIÇÃO CORPORAL NA DOENÇA DE ALZHEIMER - Silva, Juliana Maria (2021)
Introduction: In addition to Alzheimer's disease, other conditions related to physical and metal decline resulting from aging coexist in the elderly population, such as sarcopenia and osteoporosis. Although Alzheimer's disease, sarcopenia and osteoporosis can coexist in the elderly population by mere statistical coincidence, it is difficult to deny that there is a strong relationship between them. If, on the one hand, the pathophysiological mechanisms common to these three pathologies are still not completely clear, on the other hand, it is known that they share several risk factors in common. Objective: To analyze the association between nutritional status, body composition and cognitive impairment in patients with Alzheimer's disease. Material and Method: 35 elderly with Alzheimer’s disease, linked to the non-governmental organization Association of Studies, Research and Aid to Alzheimer’s Patients were evaluated, from the period of January 2018 to August 2019. The body composition from such patients was obtained through dual-energy absorptiometry. The nutritional state was also evaluated, through a mini-nutritional analysis. Results: Women presented higher total percentage of body fat (41.5% vs. 31.9% respectively, p<0.01) and higher percentage of gynoid fat (44.1% vs. 28.8% respectively, p<0.01) then men. On the other hand, men presented higher lean mass (46.8 kg vs. 33.2 kg respectively, p<0.01), higher appendicular lean mass (9.5 kg vs. 13.4 kg respectively, p<0.01) and higher index of skeletal appendicular lean mass (7.2 kg/m2 vs. 5.6 kg/m2 respectively, p<0.01) then women. Men also presented higher bone mineral content (2.5 kg vs. 1.7 kg respectively p<0.01) and higher overall bone mineral density (1.1 g/cm3 vs. 1.0 g/cm3 respectively, p<0.01) than women. Regarding the nutritional status, 64.7% of men and 44.4% of women with Alzheimer’s disease were either undernourished or at nutritional risk. Patients with Alzheimer’s disease at more advanced states (moderate to severe) obtained lower punctuation in the nutritional mini- evaluation than those with the disease at early states (23.0 vs. 25.0 respectively, p=0.02). In addition, patients with the Alzheimer’s disease at more advanced states presented lower body mass indexes than those at early stages (24.5 kg/m2 vs. 26.5 kg/m2 respectively, p=0.02). At last, there were no statistically significant differences among the patients with Alzheimer’s disease at early states and those with more advanced or severe states regarding the prevalence of overweight/obesity (75.0% vs. 44.0% respectively, p=0.15), sarcopenia (50.0% vs. 52.0% respectively, p=0.09) and osteopenia/osteoporosis (58.0% vs. 48.0% respectively, p=0.5). Conclusion: The results suggest that both body composition as well as the nutritional status of men and women with Alzheimer’s disease are different from each other. Results also show that obesity, sarcopenia, sarcopenic obesity and osteopenia/osteoporosis are common conditions in patients with Alzheimer’s disease. However, their prevalence has not been modified with the progression of the disease.